The Role of Software Engineering in Digital Transformation of Industry 4.0 - naufal, wandi; Dimas, Novario; Tauhid, Naufal; Sulistiani, Heni (LPPM STIKI Malang, 2024)
Industry 4.0 is characterized by the adoption of advanced technologies that are changing the way companies operate, interact with customers, and produce products. One of the key factors in the success of digital transformation in this era is software engineering. Innovative and flexible software is the foundation for the implementation of technologies such as the Internet of Things (IoT), artificial intelligence (AI), big data, and automation that support modern industrial operations. This article discusses the critical role of software engineering in accelerating the adoption of Industry 4.0, with a focus on developing software that supports interoperability, scalability, and security in an ever-evolving digital ecosystem. It also discusses the challenges faced by software developers, including the need for new skills, integration of legacy systems, and management of big data generated by devices and sensors. With the right software engineering approach, companies can harness the full potential of Industry 4.0 technologies to improve operational efficiency, productivity, and innovation.(Furstenau et al., 2020)